THE MARKETING MIND AND ITS IMPACT ON ACTIVATING MARKETING INTELLIGENCE APPLICABLE TO ASIACELL MOBILE COMMUNICATIONS ( )COMPANY - Assistant Professor Dr. Rabie Yassin Saud; Assistant Professor Dr. Zaid Yassin Saud (Scholar Express Journals, 2022)
This research aims to identify modern concepts in marketing, which are the marketing mind and smart marketing dimensions (digital marketing, human capital, social capital). The Asiacell Mobile Communications Company in Iraq was chosen to in this research. A questionnaire was designed and prepared for this purpose, as it included a number of the company's managers, heads of its departments, people and units in Baghdad. A set of appropriate statistical processing methods were used to analyze the data that are used to determine the level of the interactive role that finds the relationship between the independent and dependent variable. The research come up with some results, the most important of which are: the company needs to employ minds with capabilities and qualifications in order to overcome changes in the surrounding environment. The success of programs and plans needs a management with distinctive capabilities, in order to take the necessary decisions in a timely manner. In addition to the fact that the success of the smart marketing process in the company depends on the availability of a set of technical and cognitive requirements, the most important of which are achieving the benefit for consumers, the effectiveness of the services provided to them, and achieving interdependence and integration of all marketing activities
Keywords: marketing; mind; marketingsmart